University social responsibility and knowledge management for a tax culture: Perception of internal stakeholders of tax advisory centers in Peru - Joberth Vargas-Figueroa; Melva Linares-Guerrero; Sindulfo Javier Diaz-Angulo; Maria Jeanett Ramos-Cavero; Franklin Cordova-Buiza (Knowledge & Performance Management)
Developing countries generally have a poor tax culture, and in this context, university social responsibility plays an important role in knowledge management with an impact on tax collection. This study aims to determine the level of perception of University Social Responsibility (USR) by internal stakeholders (teachers, administrative staff, students) participating in the Accounting and Fiscal Support Nuclei (NAF) program (Latin American training program for university students on the tax and customs system, to provide free assistance to micro-enterprises and low-income people). The methodology applied was a quantitative, cross-sectional, non-experimental study; the sample consisted of internal stakeholders of the Northern Private University, (Peru); the sampling was probabilistic; the population was 220 people and the survey was applied to 136 people. Judges validated it using Aiken’s V and Cronbach’s Alpha reliability test, obtaining a result of 0.921. These results were processed using the IBM SPSS statistics. The results show that stakeholders attribute the USR efficiency in 88.22% to program implementation; 96.3% to the priority axes, for considering a culture of inclusion; 90.40% to management levels, for having committees, implementation of plans, projects, and management indicators; 89% to the record of actions carried out, such as the storage of evidence; 72.8% to the communication of results and impact; 92.6% to the implementation of strategies. It is concluded that the USR level of internal stakeholders based on the NAF program is efficient. The main factor is the strategies implemented by the university, with the active participation of all who contribute to improving students’ competencies.